1540. Prevalence and Risk Factors associated with HIV and Syphilis Co-infection in the African Cohort Study. (31st December 2020) - Gilbert, Laura; Dear, Nicole; Esber, Allahna L; Iroezindu, Michael; Bahemana, Emmanuel; Kibuuka, Hannah; Owuoth, John; Maswai, Jonah; Crowell, Trevor A; Polyak, Christina; Ake, Julie A
Abstract: Background: Each year, 6 million new syphilis cases are diagnosed globally. Seroprevalence studies in low-income countries (LIC) are limited but is estimated at 3.5-4.6%. Few studies have researched prevalence of sexually transmitted infections (STIs) in people living with human immunodeficiency virus (HIV; PLWH). Current guidelines for PLWH in LIC recommend STI testing for symptomatic persons and those with a new HIV diagnosis, which may lead to high rates of undiagnosed STIs. Here we provide updated STI prevalence rates and risk factors for syphilis co-infection in PLWH in the African Cohort Study (AFRICOS). Methods: AFRICOS is an ongoing longitudinal study enrolling PLWH in four African countries where participants undergo routine medical exams, sociobehavioral questionnaires, and laboratory extraction for study purposes every 6 months. Enrollment syphilis data was extracted to determine screen-positive and serologically-confirmed syphilis prevalence rates for this study. Bivariate and multivariate analysis were performed to determine risk factors for HIV and syphilis co-infection and reported as adjusted prevalence ratios (APR) with 95% confidence intervals (CI). Results: Between January 2013 and March 1, 2020, 2883 PLWH enrolled. Prevalence of screen-positive and confirmed syphilis was 5.2% and 3%, respectively. Among PLWH with confirmed syphilis, 58.6% were women, mean age was 37.8 years old (IQR 31.658, 45.011, p = 0.068), and genital ulcers were documented in 1.61% participants. In the multivariate model, participants with confirmed syphilis co-infection were more likely to have none or some primary education [2.65 (1.34, 5.230)], demonstrate impaired cognition [2.1 (1.25, 3.590], and consume alcohol [1.88 (1.19, 2.970] compared to those without syphilis. Conclusion: In conclusion, our findings suggest that syphilis rates remain elevated at endemic levels in LIC where diagnosis remains challenging. Based on our analysis, current STI guidelines for PLWH in Africa are likely leading to a large proportion of undiagnosed STIs and potentially contributing to community spread. While this study observed that lower education level, alcoholism, and impaired cognition were associated with syphilis co-infection, further studies are needed to investigate these associations. Disclosures: All Authors : No reported disclosures